Optimizing Production Planning Decisions with a Hybrid Grid Partitioning and Rough Set Approach for Fuzzy Rule Generation - Sykiotis Clifford Markou; David ugajska Hatsopoulos (International Journal of Enterprise Modelling, 2021)
This research focuses on optimizing production planning decisions using a hybrid grid partitioning and rough set approach for fuzzy rule generation. The aim is to address the challenges associated with uncertainty, complex relationships, and the need for a systematic methodology tailored specifically for production planning. The proposed approach integrates grid partitioning, rough set theory, and fuzzy rule generation to provide decision-makers with a comprehensive framework for generating robust fuzzy rules. The mathematical formulation formulates the optimization problem by considering input variables such as demand and resource availability, output variables representing production quantities, fuzzy membership functions to model linguistic variables, and fuzzy rules to capture relationships. The objective is to minimize deviations between actual and desired outputs while satisfying relevant constraints. A numerical example is presented to illustrate the application of the proposed approach. The results demonstrate improved decision-making, enhanced operational efficiency, and the applicability of the approach to various production planning scenarios. However, limitations in terms of data quality, generalizability to complex production systems, and computational complexity should be considered. Future research should address these limitations and explore real-time adaptability to further enhance the effectiveness of the proposed approach. Overall, this research contributes to the advancement of production planning methodologies by providing a structured framework for handling uncertainty, capturing complex relationships, and optimizing production planning decisions.